Incidence of and Risk Factors for Hepatic Encephalopathy in a Population‐Based Cohort of Americans With Cirrhosis. Issue 11 (6th September 2019) - Tapper, Elliot B.; Henderson, James B.; Parikh, Neehar D.; Ioannou, George N.; Lok, Anna S.
Abstract : Hepatic encephalopathy (HE) is a devastating complication of cirrhosis. Data are limited regarding the incidence of and risk factors for HE among contemporary patients in the context of the shifting epidemiology of cirrhosis. We examined a 20% random sample of U.S. Medicare enrollees with cirrhosis and Part D prescription coverage from 2008 to 2014. We modelled incident HE using demographic, clinical, and pharmacologic data. Risk factors for HE were evaluated, including demographics/socioeconomics, cirrhosis etiology, severity of liver disease, and pharmacotherapy, along with gastroenterology consultation, as time‐varying covariates. Among 166, 192 Medicare enrollees with cirrhosis followed for 5.25 (interquartile range [IQR], 2.00‐7.00) years, the overall incidence of HE was 11.6 per 100 patient‐years. The cohort's median age was 65 years (IQR, 57‐72), 31% had alcohol‐related cirrhosis, and 49% had likely nonalcoholic fatty liver disease cirrhosis. The two strongest associations with HE were alcohol‐related cirrhosis (adjusted hazard ratio [AHR], 1.44; 95% confidence interval [CI], 1.40, 1.47, relative to nonalcoholic nonviral cirrhosis) and the presence of portal hypertension (AHR, 3.42; 95% CI, 3.34, 3.50). Adjusting for confounders, benzodiazepines (AHR, 1.24; 95% CI, 1.21, 1.27), gamma aminobutyric acid (GABA)ergics (AHR, 1.17; 95% CI, 1.14, 1.21), opioids (AHR, 1.24; 95% CI, 1.21, 1.27), and proton pump inhibitors (PPIs) (AHR, 1.41; 95% CI, 1.38, 1.45) were all associated with incident HE. Only benzodiazepines, however, were associated with the risk of hospitalization with HE (incidence‐rate ratio, 1.23; 95% CI, 1.20, 1.26). Conclusion: Novel data regarding the risk of HE for contemporary patients with cirrhosis are provided. The incidence of HE in an older population of Americans with cirrhosis is high, particularly among those with alcohol‐related cirrhosis and portal hypertension. Several medication classes, namely PPIs, opiates, GABAergics, and benzodiazepines, represent potentially modifiable risk factors for HE.